Molecular Characterization Analysis of Thalassemia and Hemoglobinopathy in Quanzhou, Southeast China: A Large-Scale Retrospective Study - Zhuang, Jianlong; Zhang, Na; Wang, Yuanbai; Zhang, Hegan; Zheng, Yu; Jiang, Yuying; Xie, Yingjun; Chen, Dongmei (Frontiers in Genetics, 2021)
Background: Limited reports are available on molecular spectrum of thalassemia and hemoglobinopathy investigation in Fujian province Southeast China. Here, we aim to reveal the spectrum of thalassemia mutation and hemoglobinopathy in Quanzhou region. Methods: A total of 17,407 subjects with thalassemia trait were collected in Quanzhou region. Gap-PCR, DNA reverse dot blot hybridization and DNA sequencing were utilized for common and rare thalassemia gene testing. Results: In this study, 7,085 cases carrying thalassemia mutations were identified, the detection rate was 40.70% (7,085/17,407). Among them, 13 α-thalassemia gene mutations were identified, with the most common α-thalassemia mutations being --SEA (69.01%), followed by -α3.7 (21.34%) and -α4.2 (3.96%). Twenty-six β-thalassemia gene mutations were detected, with the mutations of IVS-II-654(C>T) (36.28%) and CD41/42(–TCTT) (29.16%) were the most prevalent. A variety of rare thalassemia variants were identified, among them, --FIL, βMalay, βIVS-I-130 and βIVS-II-672 mutations were first identified in Fujian province. Additionally, we presented 78 cases of hemoglobinopathies, Hb Owari was first report in Fujian province and Hb Miyashiro was first identified in Chinese population. Conclusion: Our study suggests a diversity of thalassemia mutations and firstly revealed the mutation spectrum of rare thalassemia and hemoglobinopathies in Quanzhou Southeast China, and contributes valuable date for prevention and control of thalassemia in Southeast China.